1999
DOI: 10.1108/03068299910230035
|View full text |Cite
|
Sign up to set email alerts
|

The impact of socio‐economic factors on gambling expenditure

Abstract: This paper examines the socio‐economic determinants of gambling expenditure on lotteries, Lotto and Instant Lotto, TAB/on‐course betting, poker machines and casino‐type games. Using a sample of 8,389 Australian households in 1993‐1994, the impact of income source and level, sex, age, ethnicity, occupational status and family composition on the decision to gamble is assessed. The results indicate that these variables exert a significant influence on the probability of households gambling. Furthermore, the effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 14 publications
1
24
1
Order By: Relevance
“…Layton and Worthington (1999), noted the relatively greater emphasis that Australian governments (particularly state) have placed on gambling related revenues than most comparable countries. They have tried to incorporate many socio-economic factors to determine gambling expenditure, of which household income was one.…”
Section: Theory and Literature Reviewmentioning
confidence: 99%
“…Layton and Worthington (1999), noted the relatively greater emphasis that Australian governments (particularly state) have placed on gambling related revenues than most comparable countries. They have tried to incorporate many socio-economic factors to determine gambling expenditure, of which household income was one.…”
Section: Theory and Literature Reviewmentioning
confidence: 99%
“…more money to spend per member of household) than those with lower ones. Several other studies have confirmed such a positive link Layton & Worthington, 1999;Tan, Yen, & Nayga, 2010). Then again, a low-income individual might regard gambling as an investment opportunity rather than entertainment.…”
Section: International Gambling Studies 97mentioning
confidence: 74%
“…Third, schools may leverage this parsimonious, quantitative model to identify, at an early stage, students relatively susceptible to problem/pathological gambling for prioritizing counseling services. Lastly, psychologists and psychiatrists may further investigate the psychological causality behind this parsimonious, quantitative model for the advancement of theories of addiction and related treatment and rehabilitation (Ladouceur, Sylvain, & Gosselin, 2007;Layton & Worthington, 1999;Nelson, LaPlante, LaBrie, & Shaffer, 2006), in particular in relation to adolescents. Furthermore, the aforementioned theoretical relationship is probably among the most general ones of its kind so far in that it is based on and derived from the full Schwartz Value Inventory (Schwartz, 1992), which is commonly regarded as one of the most general and universal models of human values.…”
Section: Discussionmentioning
confidence: 99%